MODIFICATION OF GUT BACTERIAL BILE SALT HYDROLASE ACTIVITY AND CARDIOVASCULAR RISK: A RANDOMIZED STUDY - Neverovskyi, Artem; Chernyavskyi, Volodymyr; Shypulin, Vadim; Gvozdecka, Lesya; Mikhn`ova, Nataliya (The Ukrainian Scientific Medical Youth Journal, 2020)
Introduction: secretion of bacterial bile salt hydrolase (BSH) is one of the main mechanisms by which gut microbiota play role in cholesterol metabolism. There are limiting and controversial data regarding the clear effect of gut BSH activity correction on modification of serum cholesterol and cardiovascular risk (CVR). Aim of investigation was to evaluate the relationship between modification of the gut bacterial BSH relative activity (RA) by probiotic L. plantarum and serum cholesterol with CVR levels. Methods: the study was conducted as open, comparative, randomized, parallel and included 26 almost healthy participants (healthy control group) and 77 patients with dyslipidemia and without anamnesis of major cardiovascular events, that were divided in two groups: main treatment group (n=41) received combination therapy (capsules with Lactobacillus plantarum in the amount of 2*109 CFU one time a day and tablets simvastatin 20 mg one time a day) and control treatment group (n=36) received monotherapy (simvastatin 20 mg one time a day) during 12 weeks. Before and after 12 weeks of treatment the assessment of total RA of gut BSH, lipid profile and CVR level according to 5 risk scores were performed. Results: at baseline the RA of BSH was higher in healthy adults comparing to participants with dyslipidemia (p<0,001); after 12 weeks of treatment there wasn`t difference between healthy control and only main treatment groups (р=0,45). It was found that with increasing of RA of gut bacterial BSH, the risk of failure of treatment efficacy endpoints achievement (≥20% reduction of values) decreased regarding: total cholesterol (TC) (p=0,0306), OR=0,00133 (95% CI; 3,28*10-6-0,538); low-density lipoproteins (LDL) (p<0,001), OR=5,65*10-14(95% CI; 6,38*10-20-5*10-8); CVR level according to Framingham score (р=0,0035), OR=4,09*10-5(95% CI; 4,66*10-8-0,0359); CVR level according to 2013 ACC/AHA algorithm (р=0,0135), OR=3,8*10-4(95% CI; 7,34*10-7-0,197); CVR level according to PROCAM score (p=0,00125), OR=8,38*10-6 (95%; CI; 6,93*10-9-0,0101). Conclusions: additional supplementation with BSH-producing bacteria L. plantarum was more effective in increasing of BSH activity compared to simvastatin monotherapy. Increasing of BSH RA by L. plantarum was associated with higher chances to achieve treatment efficacy goals regarding reduction of TC, LDL and CVR levels according to Framingham, 2013 ACC/AHA algorithm and PROCAM scores.